Intra‐specific relatedness, spatial clustering and reduced demographic performance in tropical rainforest trees. (20th May 2018) - Shao, Xiaona; Brown, Calum; Worthy, Samantha J.; Liu, Lu; Cao, Min; Li, Qiaoming; Lin, Luxiang; Swenson, Nathan G.
Abstract: Intra‐specific negative density dependence promotes species coexistence by regulating population sizes. Patterns consistent with such density dependence are frequently reported in diverse tropical tree communities. Empirical evidence demonstrating whether intra‐specific variation is related to these patterns, however, is lacking. The present study addresses this important knowledge gap by genotyping all individuals of a tropical tree in a long‐term forest dynamics plot in tropical China. We show that related individuals are often spatially clustered, but having closely related neighbours reduces the growth performance of focal trees. We infer from the evidence that dispersal limitation and negative density dependence are operating simultaneously to impact the spatial distributions of genotypes in a natural population. Furthermore, dispersal limitation decreases local intra‐specific genetic diversity and increases negative density dependence thereby promoting niche differences and species coexistence as predicted by theory.